Analisis Keterampilan Proses Sains Siswa Untuk Mengembangkan E-Modul Pembelajaran Berbasis Inkuiri Terbimbing - Aljunaedi Aljunaedi; Harlita Harlita; Sri Yamtinah (Universitas Sebelas Maret, 2025)
The study aims to analyze students' science process skills (SPS) as the basis for developing a guided inquiry E-Module. The method used is a mixture of qualitative and quantitative. The subjects of the study involved 94 ninth grade students of SMP Negeri 1 Kasiman Bojonegoro and 4 science teachers. Data were collected through questionnaires, interviews, and SPS tests on physical and chemical changes. The results of the analysis show that the majority of students consider science learning difficult (74.3%), memorize theory without practice (89.1%), and want practical learning (70.6%). As many as 91.8% of students need interactive teaching materials that can be accessed via digital devices. In terms of teachers, the dominant learning model is found to be lectures, limited laboratory equipment and lack of innovation in teaching materials as the main obstacles. The test results showed that 72% of students in the moderate KPS category, the indicators identifying variables (55%) and concluding (54%) had higher achievements. The conclusion of the study recommends the development of an e-module based on guided inquiry to improve students' KPS. E-Modules help students understand scientific concepts, improve analytical skills according to the needs of 21st century education.